Pengembangan Kreativitas Generasi Alpha Di Masa Covid-19 Melalui Yayasan Sanggar Genius - Ziadatun Nabila; Ahmad Syamsudin (MATAPPA: Jurnal Pengabdian Kepada Masyarakat, 2021)
This community service activity aims to develop the potential of children by providing a forum for the development of creativity for the Alpha generation through the genius studio foundation in Brengkok Brondong Lamongan Village, as well as fostering children's learning motivation. This community service activity was carried out at the Sanggar Genius Cumpleng Brengkok Foundation in Brondong Lamongan. This activity lasted for 3 weeks, this activity was followed by participants from SD/MI students in Brengkok Village. The implementation time of this Alpha generation creativity development activity is on Saturday - Monday at 13.30 WIB to 15.00 WIB. The implementation of this creative development is carried out through various stages including providing learning motivation - learning assistance - evaluation through competitions. As a result of this creativity development activity, parents find it helpful to develop their children's creativity, this activity also makes children more active, interactive and has increased self-confidence and increases children's learning motivation.